Perancangan dan Pembuatan Sistem Informasi Absensi Siswa pada SMK Negeri 7 Medan - Marthin Yohannes Simanjuntak (Jurnal Multidisiplin Indonesia, 2025)
Attendance is part of an institution's reporting activities, containing attendance data managed to find out the number of attendees at an event so that related parties can find and use it easily whenever they need it. At SMK Negeri 7 Medan there is an attendance system is still done manually, starting from recording attendance data to making reports This often results in errors resulting in inaccurate reporting. Other problems, that is, there are many things that happen in document storage, such as frequent loss of data or archives. The purpose of This practical work is to design an information system to solve this problem. Creating this attendance system uses data collection methods from SMK Negeri 7 Medan interviews field supervisor, literature studies that support problem solving and Unified Modeling Language (UML) for software design and software testing using Extreme Programming (XP) method. The results and benefits of this design are providing facilities for teachers to take attendance for students so that the processing of attendance data becomes more structured and reduce the risk of errors in student attendance data. Apart from that, students can also check attendance that has been input by the teacher.